2016
DOI: 10.1038/nn.4364
|View full text |Cite
|
Sign up to set email alerts
|

Active zone scaffolds differentially accumulate Unc13 isoforms to tune Ca2+ channel–vesicle coupling

Abstract: Brain function relies on fast and precisely timed synaptic vesicle (SV) release at active zones (AZs). Efficacy of SV release depends on distance from SV to Ca(2+) channel, but molecular mechanisms controlling this are unknown. Here we found that distances can be defined by targeting two unc-13 (Unc13) isoforms to presynaptic AZ subdomains. Super-resolution and intravital imaging of developing Drosophila melanogaster glutamatergic synapses revealed that the Unc13B isoform was recruited to nascent AZs by the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
282
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(302 citation statements)
references
References 69 publications
19
282
0
1
Order By: Relevance
“…The broad-spectrum phosphatase inhibitor OA increases SV mobility by ~10 times in hippocampal terminals (Jordan et al, 2005) or at the neuromuscular junction (Gaffield et al, 2006). In calyceal terminals, OA only increased SV mobility by ~1.4 times, similar to that recently reported at cerebellar mossy fiber terminals (~2 times; Rothman et al, 2016), suggesting higher abundancy of untethered SVs in these terminals and/or phosphorylation independent SV tethering with molecules such as Basson (Hallermann et al, 2010) or Unc analogs (Böhme et al, 2016). …”
Section: Discussionsupporting
confidence: 87%
“…The broad-spectrum phosphatase inhibitor OA increases SV mobility by ~10 times in hippocampal terminals (Jordan et al, 2005) or at the neuromuscular junction (Gaffield et al, 2006). In calyceal terminals, OA only increased SV mobility by ~1.4 times, similar to that recently reported at cerebellar mossy fiber terminals (~2 times; Rothman et al, 2016), suggesting higher abundancy of untethered SVs in these terminals and/or phosphorylation independent SV tethering with molecules such as Basson (Hallermann et al, 2010) or Unc analogs (Böhme et al, 2016). …”
Section: Discussionsupporting
confidence: 87%
“…Based on the present finding that N D and N C are equal, we propose that, at PF-MLI synapses, either 0 or 1 fusion-competent SV is docked per VGCC cluster. This model is similar to the proposed association of precisely defined docking sites with a cluster of cacophony channels at the fly neuromuscular junction (23,24) with the important difference that, in the fly, several docking sites are associated with one VGCC cluster, whereas we propose here a one-to-one stoichiometry.…”
Section: Discussionsupporting
confidence: 82%
“…16), at PF-PC synapses (32), and at amacrine cell synapses (54). Likewise, recent morphological data show an age-dependent tightening of the VGCC-SV arrangement in AZs of the fly neuromuscular junction (23).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, a similar interaction was not observed in the chick synapse using co-immunoprecipitation (Khanna et al, 2006; Wong and Stanley, 2010), and a separate study found that RIM tethering of Ca v 2 channels requires the Ca v β subunit to serve as an intermediary between the two proteins (Kiyonaka et al, 2007). Recently, evidence has emerged that Ca v 2 channel pre-synaptic scaffolding undergoes a developmental switch in Drosophila , where different mRNA splice isoforms of the vesicle priming protein UNC-13 interact with distinct scaffolding proteins for either microdomain tethering in immature synapses (i.e., with Syd-1 and Liprin-α), or nanodomain tethering in mature synapses (i.e., with Bruchpilot and RIM-associated protein complexes) (Böhme et al, 2016). Thus, although it appears as though RIM plays conserved roles in Ca v 2 channel tethering in protostome and deuterostome synapses, complex and dynamic processes are likely at play.…”
Section: Cav Channel Physiology In Basal Metazoansmentioning
confidence: 99%